2022
DOI: 10.1002/ajpa.24529
|View full text |Cite
|
Sign up to set email alerts
|

Drought, psychosocial stress, and ecogeographical patterning: Tibial growth and body shape in Samburu (Kenyan) pastoralist children

Abstract: Objectives: This study of Samburu pastoralists (Kenya) employs a same-sex sibling design to test the hypothesis that exposure in utero to severe drought and maternal psychosocial stress negatively influence children's growth and adiposity. As a comparison, we also hypothesized that regional climate contrasts would influence children's growth and adiposity based on ecogeographical patterning. Materials and Methods: Anthropometric measurements were taken on Samburu children ages 1.8-9.6 years exposed to severe d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Drought monitoring experts consider the 2008-2009 drought to be severe as measured meteorologically, in terms of rangeland, need for food aid, and with respect to livestock losseswhich were 57% for cattle and 65% for sheep 19 . Although our Samburu study partners report pregnancy as a stressful time overall, they report substantially more distress during pregnancies in the 2008-2009 drought compared to pregnancies with same-sex sibling controls conceived after the drought resolved and unexposed to severe drought in utero 20 . In Fig.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Drought monitoring experts consider the 2008-2009 drought to be severe as measured meteorologically, in terms of rangeland, need for food aid, and with respect to livestock losseswhich were 57% for cattle and 65% for sheep 19 . Although our Samburu study partners report pregnancy as a stressful time overall, they report substantially more distress during pregnancies in the 2008-2009 drought compared to pregnancies with same-sex sibling controls conceived after the drought resolved and unexposed to severe drought in utero 20 . In Fig.…”
mentioning
confidence: 66%
“…We have previously reported that severe drought exposure in utero associated to lower child body weight and higher peripheral adiposity independently of microclimate variation 20 . Additionally, we have previously reported differential epigenome-wide DNAm patterns based on severe drought exposure, as well as potential CpG sites that mediate the association between drought exposure and child body weight and potentially peripheral body fat 22 .…”
mentioning
confidence: 92%
“…Women without a male heir lose the right to livestock and can become impoverished and isolated (Fratkin & Smith, 1995). Having a male infant and the prospect for enduring access to livestock may therefore increase women's prestige and social capital (Straight et al, 2022). This in turn may increase their autonomy in health‐related decision making and therefore better maternal health outcomes (Brunson et al, 2009; Caldwell & Caldwell, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Mental health conditions were infrequently studied (n = 7) in the article set. These studies evaluated the impacts of extreme weather events and climate shocks on economic status, mental wellbeing, and psychological distress [68][69][70][71].…”
Section: Mental Health Conditionsmentioning
confidence: 99%